Nutrition profile of under-five year rural children and correlates of undernutrition in central India - Kodavalla, Venkaiah; Meshram, Indrapal I; Kodavanti, Mallikharjun Rao; Reddy, Chitty Gal; Manchala, Ravindranath; Kumar, Sharad; Kakani, Sree Ramakrishna; Avula, Laxmaiah; Veera, Brahmam Ginnela Narsimhachary (Indian Journal of Community Health, 2015)
Background: High prevalence of undernutrition in Madhya Pradesh contributing to high mortality and morbidities among young children. Aims & objectives: to assess prevalence of undernutrition and its co-relates among under 5 year children in Madhya Pradesh. Materials & Methods: It was a community based cross- sectional study carried out in all the districts of Madhya Pradesh, India using systematic random sampling. Results: A total of 22,895 children (Boys:12379, Girls:10516), mean age 26.1 months, SD 15.9, were covered. The overall prevalence of underweight, stunting and wasting was about 52%, 49% and 26% respectively. The prevalence was significantly (p<0.01) higher among boys as compared to girls. The risk of underweight, stunting and wasting was significantly higher among children belonging to SC+ST communities (OR: 1.36, 1.21 & 1.23) as compared to others, among children of illiterate parents and landless labourers (OR: 1.27, 1.32 & 1.15). The risk of stunting was significantly higher among children living in HHs without electricity (OR: 1.41) and HHs not using sanitary latrine (OR: 1.29). Similarly, the risk of wasting was significantly higher among households not having access to safe drinking water, mothers not cleaning their hands before feeding and among children with history of morbidity during preceding fortnight. Prevalence of underweight (28%), stunting (17%) and wasting (34%) was significantly (p<0.01) lower among children who were exclusively breast fed up to 6 months. Conclusions: Multiple risk factors are associated with childhood undernutrition and needs multi-pronged and multi-sector approach to tackle the problem. The results will help planners to develop and implement appropriate intervention strategies, for effective control and prevention of undernutrition among under-five year children in Madhya Pradesh